Smart kinesthetic measurement model in dance composision - Triana, Dinny Devi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This research aimed to discover a model of assessment that could measure kinesthetic intelligence in arranging a dance from several related variable, both direct variable and indirect variable. The research method used was a qualitative method using path analysis to determine the direct and indirect variable; therefore, the dominant variable that supported the measurement model of kinesthetic intelligence in arranging dance could be discovered. The population used was the students of the art of dance department and were chosen by using purposive sampling technique so that the kinesthetic intelligence could be well measured. The result of this research was that the correlation between the ability in perceiving movement and the ability in conveying movement was 3.8048. The correlation between the ability in perceiving movement and kinesthetic intelligence was 0.3137. The correlation between the ability in perceiving movement and arranging a dance was -0.3751. The correlation between conveying movement and kinesthetic intelligence was 0.1333. The correlation between conveying movement and arranging a dance was -0.2399. The correlation between kinesthetic intelligence and arranging a dance was 0.8529. These result proved that kinesthetic intelligence has significant influence to the ability in arranging a dance. It could be concluded that a smart assessment model of kinesthetic intelligence in arranging a dance that was needed should measure the kinesthetic intelligence first while the ability to perceive and convey movement became the supporting element to strengthen the kinesthetic intelligence in arranging a dance.